THE KEMA ISLAND-ARC TERRANE, EASTERN SIKHOTE ALIN: FORMATION SETTINGS AND GEODYNAMICS - Malinovsky A.I.; Golozoubov V.V.; Simanenko V.P. (My University, 2006)
The Kema Terrane is situated in eastern Sikhote Alin and extended along the coast of the Sea of Japan. The terrane is exposed in erosion windows among Late Cretaceous igneous rocks of the East Sikhote Alin volcanic belt. The terrane is composed of the Barremian (?)–Albian turbidites that contain siltstones, sandstones, gravelstones, conglomerates, mixtites, and tuff units, and basaltic volcanic flows. The Kema Terrane is thrust over the western Zhuravlevka Terrane, which is filled with the Lower Cretaceous turbidites and considered a continental-margin pull-apart basin.
Keywords: Kema terrane; Sikhote Alin; Мезозой::Меловая::Нижний::Барремский; Мезозой::Меловая::Нижний::Альбский